A tracer study on the University of the Immaculate Conception graduates of bachelor of music - EMMA V. SAGARINO; ERIC A. MORENO; T. J. E. JUAN; RENATO F. LANGOMEZ JR.; RANILLO II M. TAGIOBON; MICHELLE KAYE L. PALMES; ROSE ANGELLI B. CABIGAS (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aimed to follow up with UIC Bachelor of Music graduates working in Davao City and the surrounding area between 1996 and 2016.Methodology: A total of 31 recent college grads agreed to fill out the CHED-modified survey and contribute to the study, which used a descriptive research design and a purposive snowball sampling technique.Findings: Despite the economic downturn, 51.8% of respondents were able to secure employment within six months of graduating; the vast majority of these individuals are in the teaching profession and are therefore employed in schools or studios. Almost half (42%) of current employees are consistent, with most having heard about their positions through personal recommendations. Respondents believe their education at UIC has helped them become more marketable to potential employers because of the curriculum they have taken away from their time there and the values they have internalized.Implications/Novelty: The distribution industries in Davao City and beyond have not been studied before, and this study is the first to undertake an activity that can pinpoint the employment placement of music graduates and profile their employment/entrepreneurial endeavors.